Precipit.Ar: IDR Curves for Argentina using rainfall rate estimates from TRMM and GPM Missions (LACCEI, 2024)
One of the issues that hydraulic engineers in Argentina face when carrying out projects is the unavailability of IDF Curves or pluviographic records necessary for their development. These curves provide average precipitation rates, based on the duration of the event and the defined return period. This study, resulting from research conducted in the Hydraulic Department of the FIUBA, consisted of obtaining IDF Curves based on remote precipitation estimates from the TRMM and GPM satellite missions promoted by NASA, JAXA, and other space agencies. The resulting product, named Precipit.Ar, consists of a set of spatially distributed IDF Curves covering a large part of the Argentinean territory, limited to the parallel 50S coinciding with the spatial coverage limit of the TRMM mission. This product allows for quickly accessing estimated IDF Curves based on geographical coordinates, duration, and recurrence. With this information as a basis, the obtained data was processed, producing a temporal series of representative average precipitation intensity estimates. Then, a sample of maximum events for different durations was selected, and a probability distribution function was fitted to construct IDF Curves.